Wschodnie kontakty Feliksa i Rudolfa Nowowiejskich (Lwów - Wilno - Białowieża) - Dulisz, Ilona (Acta Polono-Ruthenica, 2018)
The activity of Feliks and Rudolf Nowowiejski plays a significant part in the history and culture of pre-war Lviv and Vilnius. In the years 1906-1912 Rudolf was a chaplain and a secretary of the Metropolitan Archbishop of Lviv J. Bilczewski. At that time Feliks entered into cooperation with music circles of Lviv where the world premiere of the oratorio Znalezienie św. Krzyża [Finding of the Holy Cross] took place. Biographies of the two brothers are also associated with Vilinius. Rudolf for many years taught Latin in the J. Slowacki Lower Secondary School. Rela- tions of Feliks with that city are primarily associated with a rapidly growing singing movement there. Melody of the Rota was until 1929 the official bugle call of Vilinius. In organ and choral music of F. Nowowiejski one can find references to the most significant symbol of the city - Our Lady of Ostra Brama painting. However, the inspirations by Białowieża wilderness produced such works as Hejnał Prezydenta R.P [Bugle call of the President of the Republic of Poland] and the triptych Teka Białowieska.